2016
DOI: 10.21873/anticanres.11150
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Expression of Cytoplasmic Polyadenylation Element Binding Proteins for the Treatment of Cancer

Abstract: Abstract. Regulated mRNA translation plays an important role in normal cellular functions and cytoplasmic polyadenylation element binding proteins (CPEBs) are the key factors that control the elongation of poly(A) tail during translation. The expression of various Translation and Cytoplasmic Polyadenylation Element Binding Proteins (CPEBs)Regulated mRNA translation plays an important role in normal cellular functions (1, 2). The translation of an mRNA is divided into three steps: initiation, elongation and ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
(207 reference statements)
0
14
0
Order By: Relevance
“…CPEBs can modulate translational activation or repression by binding to CPE mainly found in 3′-UTR. Several studies demonstrate that CPEB family members mediate malignant transformation, including glioma, colorectal cancer, and so forth 34 . While our research group firstly reported that CPEB3 involved in the regulation of liver cancer progression 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPEBs can modulate translational activation or repression by binding to CPE mainly found in 3′-UTR. Several studies demonstrate that CPEB family members mediate malignant transformation, including glioma, colorectal cancer, and so forth 34 . While our research group firstly reported that CPEB3 involved in the regulation of liver cancer progression 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically binding to cytoplasmic polyadenylation elements (CPEs), CPEBs can further recruit several functional proteins to regulate the poly(A) tail length of target mRNAs, resulting in translational activation or repression of its targets 5,6 . The C terminus, which includes two RNA recognition motif and a zinc-finger domain, is highly conserved among CPEBs 7 . While the highly variable N terminus containing regulatory sites may contribute to the distinct functions of CPEB family members 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent studies have revealed that CPEB4 was highly expressed in multiple tumor types and was involved in tumor progression and metastasis. 6 , 7 For example, CPEB4 has been reported to be markedly increased in cancer tissues and be a promising therapeutic target in metastatic colorectal carcinoma. 16 In breast cancer, CPEB4 was distinctly elevated in primary lesions compared with adjacent normal tissues and played a pivotal role in breast cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic polyadenylation element-binding protein 4 (CPEB4), a typical member of the CPEB family, is a sequence-specific RNA-binding protein and a translational regulator, which has been demonstrated to be selectively overexpressed in various malignancies. 6 Notably particularly, recent studies have reported that CPEB4 functions importantly in cancer cells’ migration and invasion in certain types of cancer, such as glioma and breast cancers, and could be exploited as a target for cancer treatment. 7 10 Nevertheless, to our knowledge, the clinical significance and biological function in GC remain undetermined and even less is known about the regulatory mechanism of CPEB4-mediated cancer progression.…”
Section: Introductionmentioning
confidence: 99%